The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18147518
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Activity Monitoring on Physical Activity, Sedentary Behavior, and Body Weight during the COVID-19 Pandemic

Abstract: Decreases in individuals’ physical activity and increases in sedentary behavior and bodyweight have been reported during the COVID-19 pandemic. The present study assessed the ability of physical activity monitoring, which may promote physical activity and discourage sedentary behavior, to mitigate these negative outcomes. An evaluation of university samples (N = 404, 40.5 ± 15.4 years) of self-reported physical activity, sedentary behavior, and bodyweight prior to the closure of campus due to the pandemic in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous studies have been conducted which investigate the influence of COVID-19 lockdowns on physical activity and behavioral changes using both subjective and objective means. Study findings among published work largely agree that COVID-19 lockdown restrictions posed a health risk due to behavioral changes resulting from altered routines (particularly for nonessential workers), reduced amount or intensity of physical activity, and increased bouts of sedentary behavior (Barkley et al, 2021;Kingsnorth et al, 2021). However, due to the nature of lockdown restrictions, such studies possess limitations associated with one or a combination of the following: reliance on self-reported measures, memory recall and candor (Buoite Stella et al, 2021); compliance (Fernández-García et al, 2021); representative demographics among participants (Kingsnorth et al, 2021;Stockwell et al, 2021); and population size; use of multiple device types and settings used to monitor activity levels (which introduced an array of measurement error due to heterogeneity; Buoite Stella et al, 2021;Germini et al, 2022).…”
mentioning
confidence: 63%
“…Previous studies have been conducted which investigate the influence of COVID-19 lockdowns on physical activity and behavioral changes using both subjective and objective means. Study findings among published work largely agree that COVID-19 lockdown restrictions posed a health risk due to behavioral changes resulting from altered routines (particularly for nonessential workers), reduced amount or intensity of physical activity, and increased bouts of sedentary behavior (Barkley et al, 2021;Kingsnorth et al, 2021). However, due to the nature of lockdown restrictions, such studies possess limitations associated with one or a combination of the following: reliance on self-reported measures, memory recall and candor (Buoite Stella et al, 2021); compliance (Fernández-García et al, 2021); representative demographics among participants (Kingsnorth et al, 2021;Stockwell et al, 2021); and population size; use of multiple device types and settings used to monitor activity levels (which introduced an array of measurement error due to heterogeneity; Buoite Stella et al, 2021;Germini et al, 2022).…”
mentioning
confidence: 63%
“…Literature has shown changes associated with pandemic-related restrictions may have resulted in decreased physical activity, increased sedentary behavior, and increased bodyweight 6,26,27 . Our results support previous literature suggesting the pandemic-related restrictions may have had a negative impact on sedentary behavior and bodyweight 6,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown changes associated with pandemic-related restrictions may have resulted in decreased physical activity, increased sedentary behavior, and increased bodyweight 6,26,27 . Our results support previous literature suggesting the pandemic-related restrictions may have had a negative impact on sedentary behavior and bodyweight 6,26,27 . Presently, we report that regardless of cell phone use individuals experienced an overall increase in weekly reported sitting as well as an increase in reported bodyweight during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…First, a larger sample of college-aged adults is needed to better identify if other factors can account for variations in physical activity behavior. Factors, such as age, weight status, athlete, non-athlete, exercise experience, and various levels of self-efficacy for physical activity and peer influence physical activity behavior 16,17,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, research also shows that college-aged adults tend to be extremely active or sedentary 15 . Not only are males more involved in physical activity but they tend to spend more time on electronics such as watching television and excessive seated cell phone activities as well 5,16,17 . It has been found that college-aged adults seem to be the most active for activities such as sports or other leisure physical activities 18 .…”
Section: Introductionmentioning
confidence: 99%